The solvability conditions for the second order nonlinear differential equation with unbounded coefficients in L2(R) - Yesbayev, A.N.; Ospanov, M.N. (KU Publ., 2021)
The article deals with the existence of a generalized solution for the second order nonlinear differential equation in an unbounded domain. Intermediate and lower coefficients of the equation depends on the required function and considered smooth. The novelty of the work is that we prove the solvability of a nonlinear singular equation with the leading coefficient not separated from zero. In contrast to the works considered earlier, the leading coefficient of the equation can tend to zero, while the intermediate coefficient tends to infinity and does not depend on the growth of the lower coefficient. The result obtained formulated in terms of the coefficients of the equation themselves; there are no conditions on any derivatives of these coefficients.
L2(R)-де шенелмеген коэффициенттері бар екінші ретті сызықтық емес дифференциалдық теңдеудің шешілу шарттары
Условия разрешимости нелинейного дифференциального уравнения второго порядка с неограниченными коэффициентами в L2(R)
Keywords: second order differential equation; nonlinear differential equation; differential equation in an unbounded domain; generalized solution; solvability